Organização e coordenação do sistema agroindustrial da mandioca na microrregião Oeste do Paraná - Goebel, Márcio Alberto (2005)
This study analyzed the current context of organization and coordination existing at the cassava agroindustrial system in Parana West Microregion from the New Institutional Economy- NIE presuppositions and the Transaction Costs Economy- TCE which region consists of a favorable environment for the cassava culture having a great number of cassava starch industries installed and hundreds of rural producers characterized as small producers who have in the cassava culture a subsistence alternative and an income generation once it until the moment does not waste high investments for its acceptance in the property being an inexpensive culture alternative for the small rural producers For that it was realized a survey with cassava producers and the cassava starch industries existing in the region aim of the study the main observable agents in the environment which results showed the existence and participation of agricultural technicians with a favoring agent for the relations strengthening among producers and cassava starch industries Through this theoretical - empiric study it was verified that the cassava agroindustrial system in Parana West Microregion is very little organized and its coordination procedure is much weak having an heterogeneity in relation to the adopted strategies among the existing cassava starch industries what has not been favorable for the adoption of a governance structure via contract for those are characterized as of low contractual guarantees Part of this presented characteristic is directly related to the existing uncertainty the low specificity of the ?cassava? active and also the low frequency in the existing transactions in the exchange relations among cassava producers and cassava starch industries The cassava chain organization and coordination process understanding is fundamental in the sector maintenance process in face of the verified problems.